Kritik sastra feminis dalam novel “Aisyah: Wanita yang Hadir dalam Mimpi Rasulullah” karya Sibel Eraslan - Nur'aini, Aisyah; Syahdan, Halbi Muhamad (Maliki Interdisciplinary Journal, 2024)
The issues of gender inequality, stereotyping and subordination of women are many. Feminism rejects all of these things, feminism is a social movement that aims to achieve equality for women. Feminism existed before feminism itself was born. The novel “Aisyah: The Woman Who Was Present in the Prophet's Dream” proves that. This study aims to pay attention to how Sibel Eraslan portrays the figure of Aisyah as the main character, explains gender relations, and reconstructs traditional Islamic narratives. The novel was written by Sibel Eraslan, originally from Turkey. Researchers use novels that have been translated into Indonesian. The research method used is descriptive qualitative. The data collection technique uses reading and note-taking techniques, reading the entire contents of the novel, then recording important data related. Then analyze the data using a feminist literary approach, which includes the exposure of female characters, the dynamics of gender relations, and the representation of women in a religious context. Based on the results of the research, it can be concluded that the novel “Aisyah: The Woman Who Was Present in the Prophet's Dream” by Sibel Eraslan contains elements of feminism and gender equality. Feminism in this novel is reflected in Aisyah's character who is smart, wise, concerned with science, and responsible. In addition, there are also statements in the novel that contain gender equality.